Integrated Islamic-Western Education as Predictor of Muslim Youths’ Moral and Academic Development - Adam Olasunkanmi Kewulere; Isiaq Oluwatosin Yahya; Basit Alabi Saliu (Indonesian Journal of Islamic Education Studies (IJIES), 2025)
This study explores the impact of integrated Islamic and Western education on youth development outcomes, specifically moral and academic growth, among Muslim youths in Lagos, Nigeria. Employing a cross-sectional design, data were collected from 84 Muslim youths in the Ajegunle-Apapa community through convenience sampling. The "Integrated Education Impact Questionnaire" (α = 0.89) assessed participants' perceptions and developmental outcomes. Although respondents expressed strong approval of integrated education (M = 4.2/5), linear regression analyses revealed no statistically significant predictive effects on either moral (R² = 0.075, p = .210) or academic (R² = 0.054, p = .185) development. The combined model accounted for only 1% of the variance (R² = 0.010), suggesting limited explanatory power. These findings highlight a critical gap between the perceived benefits of educational integration and its measurable impact on youth development. To enhance effectiveness, the study recommends curriculum reform focused on practical relevance and the adoption of longitudinal designs in future research to evaluate long-term developmental outcomes.